Exploring the Determinant Factors Affecting Families' Ability to Care for People with Schizophrenia - Daviq, Daviq Ayatulloh; Twistiandayani, Retno; Dimas Hadi, Prayoga (Universitas Nahdlatul Ulama Surabaya, 2025)
Families often lack knowledge about schizophrenia care, which hinders their ability to provide adequate support. This study explores the factors affecting families' ability to care for people with schizophrenia. It was quantitative research using a cross-sectional approach method. There were 130 samples through the purposive sampling technique. The independent variables were knowledge, behavior, motivation, health service utilization, and social support. The dependent variable was families' ability to care for people with schizophrenia. The Authors had been tested and declared the instrument valid and reliable, with a Pearson correlation value of <0.5 and a Cronbach's alpha value of >0.6. Data analysis used a multiple logistic regression test with a confidence level of 95% (α=0.05). The results found that all independent variables, knowledge (p=0.014), behavior (p=0.042), motivation (p=0.031), health service utilization (p=0.029), and social support (p=0.017), showed a p<0.05. In addition, the largest OR (Exp B) was social support, 13.288. Thus, all independent variables significantly affect the families' ability to care for people with schizophrenia. Furthermore, the most dominant factor was social support. Good social support was 13 times more likely to improve families' ability to care for people with schizophrenia. In conclusion, there is a significant influence of knowledge, behavior, motivation, health services utilization, and social support on the families' ability to care for individuals with schizophrenia. In addition, the most dominant factor affecting families' ability to care for people with schizophrenia is social support.